Research on the format-preserving encryption modes - LIU Zhe-li; JIA Chun-fu; LI Jing-wei (Tongxin xuebao)
FPE（format-preserving encryption） was discussed,and it was shown that how to reduce domain complexity was the direction of designing FPE modes.A new FPE mode named coding-then-encipher mode was proposed and its operating principle and security were described in detail,and it was pointed out that the key for this mode was finding efficient encode and decode algorithms on domain.Furthermore,a scheme under coding-then-encipher mode which can resolve FPE problem in charsn was presented,the encode and decode algorithms were described,and their efficiency were analyzed.